Pengaruh Komunikasi dan Iklim Organisasi Terhadap Kinerja Guru di MAN 1 Medan - Erly Purba (UMSU, 2023)
The purpose of this study was to analyze and describe strategic planning at Guang Ming Medan Elementary School in achieving quality education, to find out how Guang Ming Medan Elementary School implements its strategy in achieving quality education, to find out how Guang Ming Medan Elementary School conducts strategic evaluations to achieve quality education. This research was conducted at Guang Ming Elementary School Weaving Factory Street No. 72 Medan. This research uses a qualitative case study approach. Respondents in this study were school principals, vice principals, teachers, and school committees. The findings of this study are as follows (1) strategic planning in improving the quality of graduates at SD Guang Ming Medan, is very good, has fulfilled the stages, namely: a. Analysis Stage. Analysis of the internal and external environment, examines the factors that affect the quality of graduates, captures information on current and future school conditions and evaluates the results of program implementation in the previous period as material for analysis in preparing a strategic plan. b. Strategy Formulation. The formulation is carried out by a team by adjusting the conditions of the school and taking into account the expectations of stakeholders; (2) Implementation of strategic planning in improving the quality of education at Guang Ming Elementary School is carried out, namely: a. Involve stakeholders by giving authority to teachers and staff, making program announcements at the beginning of the year, holding coordination meetings, and assigning tasks according to their fields. b. Maximizing existing resources, maximizing guidance and learning both in the academic and non-academic fields and using as much as possible the facilities and infrastructure owned by schools to support the achievement of superior quality graduates; (3) Evaluation and implications of strategic planning for the quality of education at SD Guang Ming, namely: a. Internal and external evaluations by evaluating all programs that have been implemented and those that have not been implemented, evaluating graduates every year, looking at teacher professionalism, evaluating achievements, and monitoring carried out by supervisors. b. Evaluation of the implications (impact), experiencing an increase in the quality of education with indicators: increasing the effectiveness of the teaching and learning process, increasing student achievement both academic and non-academic, increasing the number of students, improving teachers, and other academic achievements.